Phenological behaviour of Vitis rotundifolia cultivars in Pinhais – PR / Comportamento fenológico de cultivares de Vitis rotundifolia em Pinhais – PR - Flávio Zanette; Luiz Antonio Biasi; Sergio Denega (Semina: Ciências Agrárias, 2010)
The aim of this work was to characterize the phenological cycle of nine Vitis rotundifolia cultivars during the 2004/2005 season. The cultivars were Bontiful, Creek, Dixie, Magnolia, Magoon, Noble, Regale, Roanoke e Topsail. The experiment was performed on an orchard implanted in 1999 at the Canguiri Experimental Station of the Federal University of Paraná in Pinhais-PR. The phenology of two adult plants of each cultivar was monitored. The recorded phenological stages were: 1) Dormant bud; 2) Swollen bud; 3) Wool bud; 4) Green tip; 5) Bud burst (first leaf appearance); 6) Two to three leaves unfolded; 7) Five to six leaves unfolded; 8) Fully developed inflorescence; 9) Trace bloom (flowerhoods detached); 10) Full flowering (50% of the flowerhoods fallen); 11) Fruit set; 12) Groat-sized berries; 13) Pea-sized berries; 14) 50% filled berries (beginning to touch berries); 15) Final size; 16) Color change; 17) Berries ripe for harvest; and 18) End of harvesting. A very long phenological cycle was observed when compared to species such as Vitis vinifera and Vitis labrusca. These evaluations allowed us to conclude that: a) there is no difference in the phenological cycle periods between bronze and dark skinned cultivars; b) cultivars presented desuniform wool bud to full flowering cycle, ranging from 25 days (‘Regale’) to 81 days (‘Creek’); c) the cultivar Regale presented the longest cycle (203 days) from full flowering to harvest and the cultivar Creek the shortest (136 days). The evaluated cultivars additionally presented desuniform ripening and a tendency to drop berries. O objetivo foi caracterizar o ciclo fenológico de nove cultivares de Vitis rotundifolia avaliadas na safra de 2004/2005. As cultivares estudadas foram as seguintes: Bontiful, Creek, Dixie, Magnolia, Magoon, Noble, Regale, Roanoke e Topsail. O trabalho foi realizado em um pomar do Setor de Fruticultura da Estação Experimental do Canguiri da Universidade Federal do Paraná, em Pinhais-PR, sendo que as cultivares foram plantadas em julho de 1999. A fenologia foi observada em duas plantas adultas de cada cultivar. Os estádios fenológicos observados foram os seguintes: 1) Gema dormente; 2) Gema inchada; 3) Gema algodão; 4) Ponta verde; 5) 1ª folha separada; 6) 2 a 3 folhas separadas; 7) 5 a 6 folhas separadas; 8) Inflorescência desenvolvida; 9) Botões florais separados; 10) 50% das flores abertas; 11) Frutificação; 12) Grãos “chumbinho”; 13) Grãos “ervilha”; 14) Meia-baga; 15) Tamanho final; 16) Mudança de cor; 17) Maturação plena; 18) Término da colheita. Constatou-se um ciclo bastante longo das cultivares da espécie estudada, quando comparada a outras espécies, como Vitis vinifera e Vitis labrusca. As avaliações realizadas permitiram concluir que: a) não há diferença do ciclo entre as cultivares de cores branca e tinta; b) as cultivares apresentam grande variação na duração da fase de gema algodão até a inflorescência desenvolvida, variando de 25 dias (‘Regale’) até 81 dias (‘Creek’); c) o período entre o aparecimento da inflorescência e a colheita foi mais longo na cultivar Regale (203 dias) e mais curto na cultivar Creek (136 dias). As cultivares desta espécie apresentam ainda desuniformidade de maturação e elevada degrana.